ANALISIS MODUL AJAR PADA PEMBELAJARAN BAHASA INDONESIA KURIKULUM MERDEKA DI SMPIT HARAPAN UMAT NGAWI - Raihani, Izzatur; Azizah, Aida (Laboratorium Pembelajaran Bahasa, FKIP Universitas Lampung, 2024)
Education plays a very important role in the progress of a nation, so efforts to improve the quality of education need to be made by the government. One of the efforts implemented is changing the curriculum that is adjusted to the development of the times, such as the independent curriculum. The independent curriculum provides flexibility for teachers in choosing and developing teaching materials, and focuses learning on developing character, competence, and student interests. This study aims to analyze the teaching module in Indonesian language learning in class VII at SMPIT Harapan Umat Ngawi using the independent curriculum. The focus of this study is on the teaching module for descriptive text material with listening elements, which is expected to improve students' understanding of descriptive texts. This study uses a descriptive qualitative method with data obtained through interviews with Indonesian language teachers and documentation in the form of a draft of the teaching module used in learning. Data analysis techniques are carried out through data reduction and presentation to draw conclusions. The results of this study are expected to provide an overview of the teaching module in the context of the independent curriculum, as well as its contribution to the efficiency and effectiveness of Indonesian language learning at SMPIT Harapan Umat Ngawi. Pendidikan memiliki peran yang sangat penting dalam kemajuan suatu bangsa, sehingga upaya peningkatan mutu pendidikan perlu dilakukan oleh pemerintah. Salah satu upaya yang diterapkan adalah perubahan kurikulum yang disesuaikan dengan perkembangan zaman, seperti kurikulum merdeka. Kurikulum merdeka memberikan keleluasaan bagi guru dalam memilih dan mengembangkan bahan ajar, serta memfokuskan pembelajaran pada pengembangan karakter, kompetensi, dan minat siswa. Penelitian ini bertujuan untuk menganalisis modul ajar dalam pembelajaran bahasa Indonesia pada kelas VII di SMPIT Harapan Umat Ngawi dengan menggunakan kurikulum merdeka. Fokus penelitian ini adalah modul ajar materi teks deskripsi dengan elemen menyimak, yang diharapkan dapat meningkatkan pemahaman siswa terhadap teks deskripsi. Penelitian ini menggunakan metode kualitatif deskriptif dengan data yang diperoleh melalui wawancara dengan guru bahasa Indonesia serta dokumentasi berupa draft modul ajar yang digunakan dalam pembelajaran. Teknik analisis data dilakukan melalui reduksi dan penyajian data untuk menarik kesimpulan. Hasil penelitian ini diharapkan dapat memberikan gambaran mengenai modul ajar dalam konteks kurikulum merdeka, serta kontribusinya terhadap efisiensi dan efektivitas pembelajaran bahasa Indonesia di SMPIT Harapan Umat Ngawi.